Voices of a Forgotten Identity. Reflections on the Visual Work of Costa Rican Artists of Chinese Origin - Calderón Herrera, Carlos (2025)
This research addresses the artistic production of prominent Costa Rican artists of Chinese descent, such as Isidro Con Wong, Otto Apuy Sirias, Edgar León Martínez, Guillermo Porras On, Man Yu, the HAPA Collective (Karen Olsen Yu, Anna Matteucci Wo Ching, and Jennifer Karczynski Tang), and the illustrator Wen Hsu. It posits that there is an intrinsic relationship between society, history, and culture that has influenced the development of these visual creators, yet this relationship has been insufficiently explored in Costa Rican art history and cultural studies, revealing a gap in the bibliography and academic research on the subject. The methodology was based on interviews and a theoretical approach from art history and cultural studies. The analysis organized the artistic work into five phases: (1) Beginnings: Reflections on Identity; (2) Art and Cultural Integration; (3) Multiplicity and Identity: Human Suit; (4) Emerging Voices; and (5) Dream, Imagine, and Create. The significance of this study lies in being one of the first to highlight the contribution of artists of Chinese descent to the construction of Costa Rican identity, in collaboration with the Confucius Institute of the University of Costa Rica.